Pipe Network Locomotion with a Snake Robot. Issue 3 (11th November 2014) - Rollinson, David; Choset, Howie
Abstract : We present a method of achieving whole‐body compliant motions with a snake robot that allows the robot to automatically adapt to the shape of its environment. This feature is important to pipe navigation because it allows the robot to adapt to changes in diameter and junctions, even though the robot lacks mechanical compliance or tactile sensing. Rather than reasoning in the configuration space of robot joint angles, the compliant controller estimates the overall state of the robot in terms of the parameters of a low‐dimensional control function, i.e., a gait. The controller then commands new gait parameters relative to that estimated state. Performing closed‐loop control in this lower‐dimensional parameter space, rather than the robot's full configuration space, exploits the intuitive connection between the gait parameters and higher‐level robot behavior. Furthermore, the ability to automatically adjust gait parameters with this controller enables more sophisticated motions that would previously have been too complex to be controlled manually.